Development of academic achievement and inhibitory control in school-going incarcerated youth offenders - Juriah Ismail (2009)
Executive dysfunction had been associated with antisocial/externalizing behavior in children and adolescence. Adolescence with poor inhibitory control and impulsiveness were less likely to succeed in school leading to poor academic achievement. As they failed to pay attention in class, inhibit distraction, follow instructions and complete assignments, their achievements in class would be affected. The current study investigated the relations between adolescences’ (youth offenders: N = 25; undergraduates: N = 25) executive functions and academic achievement in prison school and NTU respectively. Executive functions were assessed using the Stroop task which tapped on inhibitory control and arithmetic switching task which relied on shifting/cognitive flexibility. In the Stroop task, participants had to read out loud 36 inked-coloured words and in the arithmetic switching task, participants were required to add, subtract and alternate between addition and subtraction of the digit 3 to a list of numbers. One-way ANOVA and Pearson’s correlation analyses were performed. Results revealed that inhibitory control and shifting do not significantly correlate with academic grades. However, both executive functions significantly correlate with educational level (all ps < .05), even after controlling for age and gender. Positive correlation between education and executive functions supports in promoting education in prison setting with the hope to reduce future recidivisms.